Peranan Manajemen SDM Dalam Mendorong Kebangkitan UMKM Pasca Pandemi COVID-19 Pada Komunitas UMKM Kota Ambon Provinsi Maluku - Manarintar Simarmata, Ricardo (Universitas Gajah Putih, Indonesia, 2022)
The implementation of Community Service is intended to provide socialization to MSME actors to improve the quality and capacity of human resources as part of efforts to develop MSME to face tough competition, develop various MSME business opportunities and the creative economy after the Covid-19 pandemic. The main target of Community Service is the MSME community in Ambon City. This PKM activity was carried out to share knowledge about HR Management related to improving the quality of MSME institutions, as well as distributing information related to the socialization that was carried out. With this program, it is hoped that the target of MSME actors in this PKM activity can find out about good human resource management in increasing the capacity of MSMEs and the creative economy to be used as motivation in an effort to take advantage of all available opportunities. Campus academics are also expected to be a source of knowledge, liaison or interface by increasing the HR capacity of MSME actors and becoming a center of excellence in MSME business development.